2018
DOI: 10.4103/ua.ua_9_17
|View full text |Cite
|
Sign up to set email alerts
|

This challenging procedure has successful outcomes: Laparoscopic nephrectomy in inflammatory renal diseases

Abstract: In prospective study from November 2011- November 2013, we performed 44 laparoscopic nephrectomies for benign non-functioning kidney diseases. Twenty eight patients underwent laparoscopic transperitoneal nephrectomies (63.6%), ten were laparoscopic assisted (22.7%) and six (13.6%) were converted to open. Patient's age, gender, laterality and etiology of renal failure were noted. Outcomes were measured as operative time, intraoperative and post operative complications, blood loss, pain score and hospital stay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…also reported 17% conversion rate in laparoscopic nephrectomy in inflammatory benign disease which is near to our study 13 . Another study also showed conversion rate of 13.63% (6 out of 44) and their indication for conversion were also almost same as our study included profuse bleeding from hilar vessels and injury to mesocolic veins and inability to identify the kidney laparoscopically 14 . Comparing the conversion with the histopathological report 5 out of 6 converted cases were related to inflammatory benign diseases.…”
Section: Discussionsupporting
confidence: 80%
“…also reported 17% conversion rate in laparoscopic nephrectomy in inflammatory benign disease which is near to our study 13 . Another study also showed conversion rate of 13.63% (6 out of 44) and their indication for conversion were also almost same as our study included profuse bleeding from hilar vessels and injury to mesocolic veins and inability to identify the kidney laparoscopically 14 . Comparing the conversion with the histopathological report 5 out of 6 converted cases were related to inflammatory benign diseases.…”
Section: Discussionsupporting
confidence: 80%
“…These results were similar to many other studies in which patients treated with laparoscopic nephrectomy had less conversion rate, less blood loss and less hospital stay as compared to conventional open surgical procedure. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report more blood loss, mainly related with the greater complexity of the surgical technique. (16) In an initial study of 200 cases, Rassweiler et al (4) reported 7.5% conversion to open surgery, Gill et al (17) 6.6%, Srivastava et al (3) 3.2%, whereas Al-Otabi et al (18) informed 0.7%. (3,18) Conversion to open surgery is not, necessarily, considered a complication, but it does reflect the learning curve of the surgeon.…”
Section: Discussionmentioning
confidence: 99%